L’incertezza europea in tempi di pandemia. Tra la salute e l’economia - Alaminos, Antonio; Alaminos-Fernández, Paloma (SocietàMutamentoPolitica, 2023)
One of the methodological conclusions of the prospective studies is that the acceleration of social changes, in association with the greater density of interrelationships in a globalized world, results in a greater frequency of crises. Crises that feed each other increasing their intensity and amplitude of effects. Crises are defined by their causes, as well as by the type, extent, and intensity of the damage they cause, although they all share one element in common: uncertainty. Uncertainty is an emotion that, according to various psychological theories, is the generator of other emotions that are activated secondarily. Emotions such as fear, frustration, or anger. The way in which emotions affect the perception and assessment of the intervention and control exercised by the State over social life is of fundamental interest. Particularly in the potential processes of legitimation of political movements based essentially on emotional mobilization. An empirical investigation is presented here on the emotional effects generated in European societies by the 2020 pandemic crisis. Using data from the survey ZA7738, and after a critical analysis of the measurement of emotions in comparative research, a study of the relational structure of emotions is carried out. Two clusters of emotions are determined: the uncertainty-fear dimension and a second dimension of a polar nature with anger-frustration at one end and hope at the opposite. Both constructs are consistent with the emotional models considered in psychology. Finally, a structural model is specified and adjusted relating the emotional dimensions with the opinions about economy, health, and freedom. The variable that measures having been, planning to be or not expecting to be economically affected by the pandemic crisis shows significant explanatory power for frustration, opposition to the restriction of freedoms for health reasons or that the measures cause greater economic damage than the health benefits. In an opposite sense, uncertainty and fear explain a greater acceptance of the restriction of freedoms for health reasons, the opinion that the health benefit is greater than the economic damage, as well as reinforcing the emotions of anger and frustration.